PERJUANGAN PASANGAN SUAMI ISTRI DALAM MENGHAYATI JANJI PERKAWINAN KATOLIK DI TENGAH TANTANGAN EKONOMI - Yuwita, Vitus; Wijaya, Albert I Ketut Deni (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2020)
Catholic marriage is a covenant based on love. In living up marital promises, the couples face economic challenges, they must struggle to make some efforts for maintaining marriage. This study aims to explore the struggles of the couples in living up the promise of Catholic marriage. In this regard, some point that want to be explored are the appreciation of the promise of Catholic marriage, the economic challenges for married couples, the struggle of married couples in living up the promise of Catholic marriage in the midst of economic challenges. This scientific research used a qualitative research model through interview methods. The research was conducted at Mater Dei Madiun Parish. This study used five to ten years of marriage as limitation. The dynamics of young marriage life towards middle age marriage the couples experienced and faced various kinds of challenges in marriage, one of them is economic challenges. The results showed that from 10 respondents of the study (100%) the couples were able to live up the promise of marriage in the midst of economic challenges. Overall (100%) the couples also faced economic challenges, they were daily needs, paying monthly bills (electricity, water, telephone), and tuition fees. In connection with living up marriage promises and facing economic challenges, overall (100%) the respondents made effort, namely managing finances well while kept praying to the God and establishing good communication each other. From these efforts the impacts that arose were their marital life is in harmony and increasingly happy.